Effect of combination NSAID and NBUVB treatment in non‐photoadapters—A pilot study. Issue 5 (13th May 2019) - Mehta, Chintan; Mohammad, Tasneem; Mehta, Dhwani; Griffith, James; Nicholson, Cynthia; Hamzavi, Iltefat
Abstract: Background: Vitiligo is a disorder of dyspigmentation that can impact quality of life. While narrow‐band ultraviolet B (NBUVB) is an effective treatment for vitiligo, a subset of patients are unable to respond to phototherapy as they cannot photoadapt. However, nonsteroidal anti‐inflammatory drugs (NSAIDs) have been shown to increase the minimal erythema dose. Purpose: To determine whether ibuprofen allows non‐photoadapters to respond to therapeutic doses of NBUVB and maintain photoadaptation. Method: Four patients unable to tolerate NBUVB or excimer past a dose of 1000 mJ/cm 2 were enrolled in the study and given ibuprofen 400 mg prior to phototherapy, which was performed 2‐3 times a week. Patients were followed up to 72 treatments to demonstrate photoadaptation and maintenance of response to phototherapy. Patients were clinically monitored by serial photographs approximately every 12 treatments. Response to phototherapy was monitored by tracking the dose of NBUVB received at each session. Maintenance of response was monitored for six treatments after discontinuing the ibuprofen. Percent change in pigmentation was also recorded. Results: Three out of four subjects enrolled in the study were able to increase their doses of phototherapy to a therapeutic range, and subjects continued to photoadapt for six treatments after discontinuing ibuprofen. Two subjects achieved repigmentation during their course of phototherapy. Conclusion: Ibuprofen may be a safe alternative to corticosteroids for select patients with vitiligo that are unable to photoadapt. It appears that the ability to photoadapt continues once ibuprofen is discontinued, negating the need for chronic use. Enabling photoadaptation allows patients to achieve therapeutic doses of NBUVB phototherapy, leading to repigmentation and improved outcomes. Trial Registration: The trial was registered through Henry Ford Hospital IRB—No. 9744.